Suppression of glucan, water dikinase in the endosperm alters wheat grain properties, germination and coleoptile growth - Bowerman, Andrew F.; Newberry, Marcus; Dielen, Anne-Sophie; Whan, Alex; Larroque, Oscar; Pritchard, Jenifer; Gubler, Frank; Howitt, Crispin A.; Pogson, Barry J.; Morell, Matthew K.; Ral, Jean-Philippe (Wiley, 2016)
Starch phosphate ester content is known to alter the physicochemical properties of starch, including its susceptibility to degradation. Previous work producing wheat (Triticum aestivum) with down‐regulated glucan, water dikinase, the primary gene responsible for addition of phosphate groups to starch, in a grain‐specific manner found unexpected phenotypic alteration in grain and growth. Here, we report on further characterization of these lines focussing on mature grain and early growth. We find that coleoptile length has been increased in these transgenic lines independently of grain size increases. No changes in starch degradation rates during germination could be identified, or any major alteration in soluble sugar levels that may explain the coleoptile growth modification. We identify some alteration in hormones in the tissues in question. Mature grain size is examined, as is Hardness Index and starch conformation. We find no evidence that the increased growth of coleoptiles in these lines is connected to starch conformation or degradation or soluble sugar content and suggest these findings provide a novel means of increasing coleoptile growth and early seedling establishment in cereal crop species.